Application of New Flotoreagents in the Enrichment of Sulfide Ores (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
As a result of the conducted research, a recommended scheme for flotation of copper ores with new reagents was developed, and a flotation concentrate with a yield of 1.55% was isolated, containing 26.7% copper and 42.35% sulphur while extracting 83.5% copper and 16.8% sulphur.